The quality of practice guidelines for melanoma: A methodologic appraisal with the agree ii and agree-rex instruments - Steeb, Theresa; Wessely, Anja; Drexler, Konstantin; Salzmann, Martin; Toussaint, Frédéric; Heinzerling, Lucie; Reinholz, Markus; Berking, Carola; Heppt, Markus (Cancers, 2020)
Multiple guidelines on cutaneous melanoma (CM) are available from several consortia and countries. To provide up-to-date guidance in the rapidly changing field of melanoma treatment, guideline developers have to provide regular updates without compromises of quality. We performed a systematic search in guideline databases, Medline and Embase to identify guidelines on CM. The methodological quality of the identified guidelines was independently assessed by five reviewers using the instruments “Appraisal of Guidelines for Research and Evaluation” (AGREE II) and “Recommendation EXcellence” (AGREE-REX). We performed descriptive analysis, explored subgroup differences using the Kruskal–Wallis (H) test and examined the relationship between distinct domains and items of the instruments with Spearman’s correlation. Six guidelines by consortia from Australia, France, Germany, Scotland, Spain and the United States of America were included. The German guideline fulfilled 71%–98% of criteria in AGREE II and 78%–96% for AGREE-REX, obtaining the highest scores. Deficiencies in the domains of “applicability” and “values and preferences” were observed in all guidelines. The German and Spanish guidelines significantly differed from each other in most of the domains. The domains “applicability” and “values and preferences” were identified as methodological weaknesses requiring careful revision and improvement in the future.
CRIS-Team Scopus Importer:2020-06-26
Keywords: AGREE; Cutaneous melanoma; Level of evidence; Melanoma treatment; Practice guideline